AN ANALYSIS OF VILLAGE ASSET MANAGEMENT IN ACCORDANCE WITH MINISTER OF HOME AFFAIRS REGULATION NO. 1 OF 2016: A CASE STUDY OF LEREPAKO VILLAGE, SOUTH KONAWE REGENCY - Kolewora, Riezkifli (Journal Economics Technology And Entrepreneur, 2024)
This study aims to identify and analyze the process of managing rural assets in Lerepako Village, South Konawe Regency, based on the Regulation of the Minister of Home Affairs Number 1 of 2016 concerning Rural Asset Management. The approach used is descriptive qualitative method with primary data obtained through interviews and secondary data from documentation. The results showed that the management of rural assets in Lerepako Village has been running quite well, but not yet fully in accordance with applicable regulations. There are several inhibiting factors in optimizing the management of rural assets, including the low competence of human resources (HR), the lack of communication related to the application of regulations, the absence of legal certainty over some assets, the lack of compliance of implementers with the rules, and the existence of unilateral claims on rural land. In addition, weaknesses in recording and administering assets and the lack of organizational commitment also affect the effectiveness of rural asset management. These findings indicate the need for human resource capacity building, socialization of regulations, and strengthening of the asset administration system at the rural level.